Compensação tributária: ilegalidade da imposição de restrições ao aproveitamento do crédito tributário e sua transferência a terceiros - Rabello, Luzia Corrêa (2010)
This study aims to examine the institution of tax compensation, considered one of the conditions for the settlement of the tax credit, in this art. 156 of the Tax Code, that since the enactment of Law No. 8383/1991, allowed discussions on the subject, spreading it in the legal system. The compensation does not match the number for tax administration designed by the taxpayer, but subjective right patriotic. The restrictions imposed by tax authorities and are remarkably unjustified, unreasonable and illegal, motivated only by the contempt of that body governing tax laws and constitutional provisions that ensure unquestionable rights to the taxpayer, for example, be entitled to recover the amounts improperly collected or more than due. For purposes of compensation are invalid restrictions on the transfer of credits to third parties for debts related to taxes and contributions administered by the Federal Revenue in Brazil, continuing in full force and effect the ability of taxpayers make their compensation in accordance with the dictates laid down in the array of legal compensation tax, namely, the Law No. 9430/96, art. 74. Purely administrative acts are not able to change the standard of public law, published with support in legal norm, which makes no restriction on the compensation tax. Finally, we show that taxpayers are entitled to use the tax credits and noticed that there are no restrictions for regulatory purposes insert in Article 170-A of the Tax Code, for the enjoyment of such claims does not match the compensation tax, only the credit mechanism -current account debit tax